Political gestures. The aristocracy against the democratic monarchy of Amadeo of Savoy - Raquel Sánchez (Pasado y Memoria, 2019)
The model of monarchy that was designed during King Amadeo’s reing in Spain presented important differences with respect to the monarchy of Isabella II. Politically, it was based on democratic political principles. Socially, in a bourgeois respectability that referred to an austere lifestyle, in line with the mentality of the middle class. The objective of this article is to try to evaluate what were the limitations of that democratic project of monarchy in a context in which its proposals were unknown in Spain. In particular, the article revolves around the role played by the upper classes (traditional supports of the monarchy), not in their conspiratorial work, but in their explicit rejection of what the democratic monarchy meant.